Effects of executive functions on consecutive interpreting for Chinese-Japanese unbalanced bilinguals - Song, Qichao; Song, Ting; Fei, Xiaodong (Frontiers in Psychology, 2023)
Introduction Previous research on performance in interpreting has focused primarily on the influence of interpreting experience on executive functions, such as shifting, updating, and inhibition. However, limited research has explored the effects of executive functions on performance. Understanding how different executive functions affect interpreting performance can provide valuable insights for teaching methods. Therefore, the present study aims to examine the effects of executive functions on comprehension and output performance during bidirectional consecutive interpreting between Chinese and Japanese. Methods This study involved 48 Chinese advanced Japanese language learners. Self-assessment results indicated that all participants were unbalanced bilingual individuals. All participants took part in consecutive interpreting, completed comprehension tests, and underwent executive function tests. Executive functions were assessed using the color–shape switching task, 1–back task, and Stroop task. Results Analysis using Bayesian linear regression revealed the following. (1) Updating exhibited a significant impact on both Japanese-to-Chinese and Chinese-to-Japanese interpreting, indicating that higher updating ability was associated with better interpreting performance. (2) Inhibition showed a significant effect on Japanese-to-Chinese interpreting performance, whereas the effect was not significant in Chinese-to-Japanese interpreting. (3) No significant effects of shifting were observed in either Japanese-to-Chinese or Chinese-to-Japanese interpreting. Discussion The results indicate that executive functions have different effects on the interpreting performance of unbalanced bilinguals, while these effects are also influenced by the direction of the source language. Based on these findings, it is recommended that executive function training should be included in interpreter teaching and training programs, with a specific focus on the updating and inhibition functions.